2022
DOI: 10.1186/s41687-022-00434-1
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life in patients with COVID-19; international development of a patient-reported outcome measure

Abstract: Background We aimed to create a questionnaire to assess the health-related quality of life including functioning, symptoms, and general health status of adult patients with current or previous COVID-19. Here, we report on Phase I and II of the development. Methods Internationally recognized methodology for questionnaire development was followed. In Phase I, a comprehensive literature review was performed to identify relevant COVID-19 issues. Decisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 40 publications
(29 reference statements)
0
20
0
Order By: Relevance
“…Due to significant uncertainty and worry, the COVID-19 pandemic has worsened psychological wellness (26). In addition, persons encountered huge changes in their everyday lives, such as social isolation and home confinement, which dramatically reduced health-related quality of life (HRQoL) (27). In this context, earlier research has demonstrated that HRQoL has decreased as a result of the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Due to significant uncertainty and worry, the COVID-19 pandemic has worsened psychological wellness (26). In addition, persons encountered huge changes in their everyday lives, such as social isolation and home confinement, which dramatically reduced health-related quality of life (HRQoL) (27). In this context, earlier research has demonstrated that HRQoL has decreased as a result of the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, earlier research has demonstrated that HRQoL has decreased as a result of the COVID-19 pandemic. There has been increased attention on the psychological impact of disease both during and after discharge from the hospital in more recent publications (27)(28)(29). Post-acute COVID-19 patients in rehabilitation were still experiencing physical and psychological symptoms, and their HRQoL was significantly lower (27,30).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In April 2020, our multilingual and multicultural research group, involving clinicians, psychometricians, statisticians, and HRQoL specialists, set out to develop a questionnaire to assess HRQoL and symptoms in patients with COVID-19, from diagnosis through active disease and recovery. The first two phases of the questionnaire development have been published [ 9 , 23 ]. In this paper, we present the next phase of the development process with pretesting of our provisional COVID-19 questionnaire and preliminary psychometric testing of the validity and reliability in an international sample of patients.…”
Section: Introductionmentioning
confidence: 99%